A geometric dual of F-maximization in massive type IIA - Christopher Couzens; Alice Lüscher (Journal of High Energy Physics)
Abstract Using equivariant localization we construct a geometric dual of F-maximization in massive type IIA supergravity. Our results use only topological data to quantize the fluxes, compute the free-energy and conformal dimensions of operators in the dual field theory without the need for explicit solutions. We utilize our formalism to study various classes of solutions, including examples where an explicit solution is not known.